Disruption of KCC2 in Parvalbumin-Positive Interneurons Is Associated With a Decreased Seizure Threshold and a Progressive Loss of Parvalbumin-Positive Interneurons - Herrmann, Tanja; Gerth, Melanie; Dittmann, Ralf; Pensold, Daniel; Ungelenk, Martin; Liebmann, Lutz; Hübner, Christian A. (Frontiers in Molecular Neuroscience, 2022)
GABAA receptors are ligand-gated ion channels, which are predominantly permeable for chloride. The neuronal K-Cl cotransporter KCC2 lowers the intraneuronal chloride concentration and thus plays an important role for GABA signaling. KCC2 loss-of-function is associated with seizures and epilepsy. Here, we show that KCC2 is expressed in the majority of parvalbumin-positive interneurons (PV-INs) of the mouse brain. PV-INs receive excitatory input from principle cells and in turn control principle cell activity by perisomatic inhibition and inhibitory input from other interneurons. Upon Cre-mediated disruption of KCC2 in mice, the polarity of the GABA response of PV-INs changed from hyperpolarization to depolarization for the majority of PV-INs. Reduced excitatory postsynaptic potential-spike (E-S) coupling and increased spontaneous inhibitory postsynaptic current (sIPSC) frequencies further suggest that PV-INs are disinhibited upon disruption of KCC2. In vivo, PV-IN-specific KCC2 knockout mice display a reduced seizure threshold and develop spontaneous sometimes fatal seizures. We further found a time dependent loss of PV-INs, which was preceded by an up-regulation of pro-apoptotic genes upon disruption of KCC2.